Die gemusterten Glasperlen und Anhänger Verucchios (Emilia-Romagna, Italien) des 8.-7. Jhs. v. Chr.: Gliederung, chronologisches Auftreten und Kontakte - Koch, Leonie C. (Römische Mitteilungen, 2024)
The study of Early Iron Age glass beads sheds light on a wide variety of aspects – from production techniques and long-distance contacts to their consumption in the graves. For regional and supra-regional comparisons, a photographic documentation and publication with a basic classification is a prerequisite, which this study seeks to contribute to. Beads and pendants with complex decorations are presented here, classified and parallels made. The investigation reveals contacts with Etruria and southern Italy, but also with the Hallstatt area, Poland and the opposite side of the Adriatic. Of particular interest are technically difficult forms already present in the 8th century B.C. and possible imported finds such as the bird beads and a faience bead. A brief outline is also given of the chronological occurrence of all Verucchio bead forms and a first reading of their use in burial customs during the 8th–7th centuries B.C. presented. A bead of the Final Bronze Age was also integrated here.